The Role of Financial Distress, Profitability and Leverage on Accounting Conservatism - Iskandar, Romi; Afriyenis, Winda; Utari, Tri Suci (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This study aims to determine the effect of financial distress, profitability and leverage on accounting conservatism in Manufacturing Companies in the Consumer Goods Industry listed on the IDX for the 2017-2021 period. The type of research used is quantitative research. The data used is secondary data. The population is 63 companies and the sample technique uses purposive sampling method. Obtained a sample of 46 companies x 5 years = 230 financial statement data. The analysis used is the classical assumption test analysis method, panel data regression analysis and hypothesis testing.The results of this study prove that financial distress during the 2017-2021 research period has a significant influence on accounting conservatism, so that financial distress can affect the level of accounting conservatism in companies. The coefficient of the regression direction of financial distress is negative, meaning that when a company experiences financial distress it will encourage managers to reduce the level of accounting conservatism. Profitability was found to have no significant effect on Accounting Conservatism. Companies that have a high level of profitability will not tend to choose conservative accounting methods. Likewise leverage was found to have a significant effect on Accounting Conservatism. The higher the level of debt owned by the company means that the company's financial condition is not good, so managers tend to increase profits so that the financial condition looks good to creditors.